Large-scale conservation: engaging agencies, organizations, landowners and funders - Manes, Robert, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The concept of affecting conservation at large scales is relatively simple: If strategies can be applied across traditional boundaries, then fragmenting effects of development and land management can be ameliorated for species that rely on large and intact habitats. The challenge, however, is that landscapes have multiple ownerships and land uses, and conservation entities often are insular. Individual organizations and agencies often lack resources, expertise, authority, and relationships essential to success. Agencies, non-government organizations, and landowners may exist in the same geographies without developing cooperative relationships necessary for large-scale conservation. Three case studies illustrate how this can be overcome. Common success factors include strong partnerships between government, non-government organizations, and landowners; and building broad recognition of the projects' merit. The case studies examined here include Montana's Rocky Mountain Front, Fortin Chacabuco Ranch near the Argentina-Chile border, and eastern Kansas' Flint Hills. In each case, the need for large-scale conservation is illuminated by one or more wide-ranging non-migratory species, and by a still-intact ecosystem that is significantly diminished across its former geographic expression. Also, in each case, conservation success resulted from either purposeful, or initially chance, cooperation between government agencies, NGOs, funders, and private landowners. This cooperation precipitated support for the projects, but also understanding among diverse and sometimes opposing interests. The purpose of this presentation is to strengthen the conservation community's ability to strategically and purposefully form and deploy the alliances necessary to achieve lasting large-scale conservation.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presented during Welcome Remarks & Plenary Session I.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses